Analysis of Higher Education Management Policy Through the Implementation of Total Quality Management - Ahmad Qurtubi (STAI Hubbulwathan Duri, 2022)
This study aimed to determine the extent to which complete quality management is applied in distance education in higher education. This research uses policy research methods. This research approach is qualitative with the type of policy research. Policy research is conducting or analyzing core social problems to provide recommendations to decision-makers on how to solve them realistically. According to research findings, Total Quality Management (TQM) in higher education manifests itself in interactions between professors and students in the classroom or in revising accreditation or assessment criteria. A structured system can turn an organization into a learning organization. TQM also contributes to increased morale, cost savings, organizational performance, and responsiveness to customer needs in higher education. Barriers to applying TQM in universities include idealistic goals, lack of agreement on the definition and application of quality, freedom, academic maturity, and administrative abilities.